2011
DOI: 10.1186/1750-1326-6-1
|View full text |Cite
|
Sign up to set email alerts
|

Localization of sequence variations in PGC-1α influence their modifying effect in Huntington disease

Abstract: BackgroundHuntington disease (HD) is caused by a polyglutamine expansion of more than 35 units in the huntingtin protein. This expanded repeat length inversely correlates with the age-at-onset (AAO), however, additional genetic factors apart from the expanded CAG repeat size are thought to influence the course and the AAO in HD. Until now, among others, the gene encoding PCG-1α (PPARGC1A) was shown to modify the AAO in two independent, however small, populations. PGC-1α is involved in the induction of various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 36 publications
0
68
0
Order By: Relevance
“…Supporting the role of PGC-1a gene in HD, it has also been implicated as a candidate modifier gene in HD; indeed, a number of variations demonstrated modifying effects on the age at onset (AO) (Taherzadeh-Fard et al 2009;Weydt et al 2009;Che et al 2011;Soyal et al 2012). Among them, the rs7665116 polymorphism has been proven to have significant association with AO, i.e., its presence was related to a protective effect in three European HD cohorts (Taherzadeh-Fard et al 2009;Weydt et al 2009;Che et al 2011).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Supporting the role of PGC-1a gene in HD, it has also been implicated as a candidate modifier gene in HD; indeed, a number of variations demonstrated modifying effects on the age at onset (AO) (Taherzadeh-Fard et al 2009;Weydt et al 2009;Che et al 2011;Soyal et al 2012). Among them, the rs7665116 polymorphism has been proven to have significant association with AO, i.e., its presence was related to a protective effect in three European HD cohorts (Taherzadeh-Fard et al 2009;Weydt et al 2009;Che et al 2011).…”
Section: Discussionmentioning
confidence: 97%
“…Among them, the rs7665116 polymorphism has been proven to have significant association with AO, i.e., its presence was related to a protective effect in three European HD cohorts (Taherzadeh-Fard et al 2009;Weydt et al 2009;Che et al 2011). However, Ramus et al could not confirm these results (Ramos et al 2012), which contradiction may be explained by the difference in the genetic backgrounds of the different populations examined.…”
Section: Discussionmentioning
confidence: 98%
“…These ubiquitous trans-membrane proteins have diverse biological roles in wnt signaling pathway, calcium channel regulation, cell adhesion, apoptosis, neurite outgrowth and synaptic plasticity [51, 52] (reviewed in [53]). There is now evidence that PSs may also play a role in mediating autophagy.…”
Section: Presenilins As Autophagy Modulatorsmentioning
confidence: 99%
“…A recent study indicated an important role of PGC-1α in AD (Sheng et al, 2012), Parkinson disease (PD) (Shin et al, 2011), Huntington disease (HD) (Cui et al, 2006; Johri et al, 2011), and amyotrophic lateral sclerosis (ALS) (Liang et al, 2011; Zhao et al, 2011) as well as diabetes (Benton et al, 2010). Single-nucleotide polymorphisms in PPARGC1A , the gene encoding PGC-1α, are associated with the age onset in HD and PD (Clark et al, 2011; Che et al, 2011), and with conversion from impaired glucose tolerance to diabetes (Esterbauer et al, 1999). The PGC-1α null mouse displays severe systemic mitochondrial and metabolic abnormalities, and spongiform neurodegeneration (Lin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%